Health Status of Traffic Police in Kathmandu Valley - Mukul Dhakal; Rakesh Kumar Shah; Nayan Kamal Sainju; Naresh Manandhar (Occupational Health and Safety Society of Nepal, 2017)
Background: Traffic Policeman are constantly exposed to health hazards due to their occupation. They are at risk of developing various diseases due to exposure to noises, dust, gases, fumes etc. during their work. Objectives of this study was to find out the health status of traffic police and common health problems due to their occupation. Methods: This cross sectional study was conducted among Traffic Police of Kathmandu Valley. Convenient sampling technique was used. A structured questionnaire was used to assess prevalence of musculoskeletal disorders, acute respiratory tract infection, skin allergy, eye problems, ear problems, utilization of safety measures and health seeking practice. Patient Health Questionnaire-9 was used for the assessment of status of depression. Clinical Examination was done by medical doctors to determine common physical health problems. Data were entered and analyzed in Statistical Package for the Social Sciences version 20. Results: A total of 296 traffic police were enrolled in the study with mean age of 31.07 years. Burning Eyes or Tearful Eyes was complaining of 72.3% of the respondents and almost two-fifth complained of some problem in vision. Nearly nine out of 10 respondents (87.8%) had musculoskeletal pain in at least one part of the body (neck, shoulder, elbow, wrist/hands, upper back, lower back, hip/thigh, knee and ankle) with major problem being upper and lower back pain. Based on PHQ-9 Questionnaire, it was found that 58.8% of the respondents were in state of some kind of depression. Conclusion: Traffic Police are constantly exposed to health hazards due to their occupation. The prevalence of musculoskeletal, ocular and hearing problems was higher among them. Awareness progarmmes should be carried out targeting them regarding the preventive measure, use of personal protective devices and regular health check-up.